Effects of sarcopenia on in-hospital results and mid-term follow-up in patients with coronary artery disease and COVID-19 - Erkan, Merve; Zengin, İsmet (The European Research Journal, 2024)
Objectives: Sarcopenia is associated with atherosclerosis, vascular dysfunction, and poor in-hospital prognosis in the general COVID-19 population. Coronary artery disease (CAD) is also associated with poor prognosis in patients with COVID-19, however, the influencing factors in this association have not yet been fully documented. This study aimed to evaluate the effect of sarcopenia on both in-hospital acute-term and mid-term follow-up clinical results in patients with CAD and COVID-19. Methods: The study population was selected from the general COVID-19 population. It consisted of 50 patients with CAD (group I) and 80 age- and gender-matched patients without CAD (group II). In-hospital acute term endpoints were determined as intensive care unit (ICU) admission, intubation, mortality, and its combination. Mid-term follow-up was also made for three-month. Sarcopenia was assessed by indexed skeletal muscle mass at T12 vertebrae level (T12-SMI) on initial chest computed tomography. Multivariable logistic regression analysis was used to detect independently related factors to endpoints. Results: Group I had more severe COVID-19 disease and a higher rate of hospitalization, ICU admission, intubation as well as mortality compared to group II in acute-term. T12-SMI was lower and sarcopenia was more frequent in group I than in group II. During the three-month mid-term follow-up period, no additional adverse results occurred in both groups. In multivariate regression analysis; sarcopenia was independently related to in-hospital combined endpoint. Conclusions: Sarcopenia is associated with in-hospital combined endpoint in patients with CAD during acute-term of COVID-19. However, it has no effect on three-month mid-term follow-up.